The Role of Spinal Cord Stimulation (SCS) in the Management of Failed Back Surgery Syndrome (FBSS) - a Comprehensive Literature Review - Paweł Połujański; Joanna Kowal; Piotr Cyran; Anna Jaroszyńska; Filip Jaroszyński; Jan Paleczny; Robert Parobczak; Joanna Winciorek; Adrianna Wiśniewska (Kazimierz Wielki University, 2024)
Study Design   A literature review.   Objective   The assessment of the efficacy of Spinal Cord Stimulation (SCS) in treatment of Failed Back Surgery Syndrome (FBSS) in terms of chronic pain management, reducing the use of pain medication, improvement of the overall quality of life and cost-effectiveness of the method in comparison to conventional medical management (CMM) and spinal revision surgery.   Methods   A review of the clinical data from prospective studies, clinical trials and systematic reviews was conducted to provide on overview of the effectiveness of Spinal Cord Stimulation (SCS) in treatment of Failed Back Surgery Syndrome (FBSS).   Results and Conclusion   Numerous studies have proven the efficacy and safety of SCS in this patient population, in terms of managing neuropathic pain, reduction of pain medication use, quality of life improvement and cost-effectiveness as compared to CMM and re-operation. Careful preoperative patient selection and psychological screening is required in order to ensures optimal treatment results.